Association of income and educational attainment in hospitalization events in atrial fibrillation - Tarryn Tertulien; Yimin Chen; Andrew D. Althouse; Utibe R. Essien; Amber Johnson; Jared W. Magnani (Elsevier, 2021)
Objective: Social determinants contribute to adverse outcomes in cardiovascular and non-cardiovascular conditions. However, their investigation in atrial fibrillation (AF) remains limited. We examined the associations between annual income and educational attainment with risk of hospitalization in individuals with AF receiving care in a regional health care system. We hypothesized that individuals with lower income and lower education would have an increased risk of hospitalization. Methods: We enrolled a cohort of individuals with prevalent AF from an ambulatory setting. We related annual income (≤$19,999/year; $20,000-49,000/year; $50,000-99,999/year; ≥$100,000/year) and educational attainment (high school/vocational; some college; Bachelor's; graduate) to hospitalization events in multivariable-adjusted Cox proportional hazards models, using the Andersen-Gill model to account for the potential of participants to have multiple events. Results: In 339 individuals with AF (age 72.3 ± 10.1 years; 43% women) followed for median 2.6 years (range 0-3.4 years), we observed 417 hospitalization events. We identified an association between both income and educational attainment and hospitalization risk. In multivariable-adjusted analyses which included educational attainment individuals in the lowest annual income category (≤19,999/year) had 2.0-fold greater hospitalization risk than those in the highest (≥100,000/year; 95% Confidence Interval [CI] 1.08-4.09; p = 0.03). In multivariable-adjusted analyses without adjustment for income, those in the lowest educational attainment category (high school/vocational) had a 2-fold increased risk of hospitalization relative to the highest (graduate-level; 95% CI 1.12-3.54, p = 0.02). However, this association between education and events was attenuated with further adjustment for income (95% CI 0.97-3.15, p = 0.06). Conclusions: We identified relationships between income and education and prospective risk of hospitalization risk in AF. Our findings support the consideration of social determinants in evaluating and treating socioeconomically disadvantaged individuals with AF to reduce hospitalization risk.